Combining Hyperspectral Imaging and a Transparent Hydroponics Bed to Analyze Growth and Age Distribution Dynamics of Entire Root Systems in Leafy Vegetables under In Situ Production Conditions - Ziyi Jin; Daisuke Yasutake; Yuki Sago; Tadashige Iwao; Gaku Yokoyama; Tomoyoshi Hirota (HortScience)
Existing methods of observing plant roots are often limited by their inability to monitor the physiological information of root system under actual agricultural conditions. To address this limitation, we developed a novel method that enables nonlaboratory monitoring of the growth characteristics of crop root systems. This study explored the application of hyperspectral imaging technology to analyze the dynamic growth and aging of root systems throughout the cultivation period, specifically focusing on spinach (Spinacia oleracea L., cv. Wase Kurone Horenso) roots in a transparent hydroponics bed in a nutrient film technique (NFT) system. Root systems of spinach grown in the transparent bed were observed daily using a hyperspectral camera. An optimal index for the classification of root ages (days after emergence) was determined as the ratio of reflectance at 498 and 601 nm. Additionally, the distribution of root age was visualized over the entire cultivation period and showed the daily dynamics of root growth and aging. This study is useful for analyzing not only the growth but also the proportion of roots at different ages in the entire root system. This deepens our understanding of root development in soilless farming environments and provides an efficient, nondestructive technique for evaluating root vitality and developmental patterns.